Multicultural Intensity: The Case of Jewish and Arab Students. (6th June 2012) - Shamai, Shmuel; Hager, Tamar
Abstract : This paper introduces a new methodology for measuring multicultural levels/intensity based on a study on attitudes towards multiculturalism conducted among college students in Israel. We developed an innovative methodological tool, "multicultural intensity, " that is composed of 8 different scales: the presence of two nationalities and cultures in the college; social friendships between Arabs and Jews on campus; studying in joint classes; ways of providing assistance to students for whom Hebrew is not their mother tongue; legitimization to deal with political and social topics within the academy; classroom curriculum; multicultural tools; reality and political views toward the Arab minority in Israel. We found that Arab and Druze groups manifested more support for multicultural policies than Jewish groups. The paper suggests that "multicultural intensity" will enable researchers and practitioners to collect knowledge as to the success/failure of multicultural policies and programs among various audiences and subsequently could improve their implementation.